A praça no contexto de pequenas cidades da microrregião de Campo Mourão - PR - Corneli, Vanessa Medeiros (2013)
The squares are elements common to the cities, regardless of the size. However contemporarystudies dealing with the dynamics of public spaces point some distance from the peopleregarding to these sites, ie, the social function of the squares would have little expressiveness.This can be mainly explained by the appearance of other forms of leisure and socializationspaces, such as shopping malls, and/or by the lack of maintenance of public policies forconservation of these sites. However the most part of these studies have urban centers ofmedium and large size as reference, not representing the peculiar condition of the smallmunicipalities. Thus, the square has become the object of study in this thesis in a differentpart of the urban, the one of the small municipalities. The most part of the Brazilianmunicipalities, 70.4%, is considered to be small, and this proportion is even higher in Paranastate, because 78.2% have less than 20,000 inhabitants (IBGE, 2010). By these data it ispossible to note the representative and meaningful role of these cities in the national contextand also in the state of Paraná. Although scientific research related to this part of the urbanhas been treated intensely in the recent years, its daily routine is still little explored and knownby the science. This condition raises interrogatives about their dynamics and socio-spatialpractices developed. Thus, this thesis sought to present the uses, functions and importance ofthe squares in small municipalities, ie, the forms of ownership, the relationships establishedbetween the citizens and this public space. It was assumed two hypotheses: a) these publicsites are characterized as a place of meeting and socializing, contradicting what occurs inmedium and large centers; b) and even in simplified forms ? shopping malls are not present -there are also alternative leisure spaces that compete with the squares in these localities. Theempirical study has as reference Peabiru, Araruna and Engenheiro Beltrão, threemunicipalities of the Center-West Meso-region of Paraná State, specifically of the Microregionof Campo Mourão. The municipalities present similar characteristics amongthemselves in relation to their origin, geographical area, period of emancipation, evolutionand population size. The ordering of the research was taken from theoretical review about therelevant subject; historical-social characterization of the three cities involved in the analysis;diagnosis of 20 squares objects of research - from observations, surveys, interviews withpioneers, informal conversations with citizens, users of squares and analysis of officialdocuments of the municipalities -; qualitative and quantitative evaluation of equipment,furniture and vegetation present in these public sites; analysis of toponimic referential; andresults of an opinion survey, conducted with 673 citizens, being 270 in Peabiru, 211 inAraruna and 192 in Engenheiro Beltrão. As a result of the research, it can be stated that thesquares are not the priority of the public management due to the precariousness in whichmany of them are found, a fact that becomes worse in public sites that are more distant fromthe central area. The vegetation condition also indicates the lack of planning in the creationand management of these spaces, because it was found to be common the presence of exoticinvader species, with potential of toxicity, in addition to the situations that do not satisfysafety and accessibility standards. However, even in non-ideal conditions of appropriation,squares are characterized as venue and socialization places, since this was the main reasongiven by participants of the survey when asked about the reasons that lead them to attend the7squares of the urbe, confirming the first hypothesis established. This observation is alsoreinforced when considering other factors such as: what do the citizens most like in the squarethat frequent, once "people/the possibility of meeting" are among the most frequently citedresponses; the period of the day that they usually go to the square, being the nocturnal one themost mentioned, ie, there is a link of the square as leisure space destination in free moments,and not only a void space in the urban area; and the period of time that the user stays on thepublic site, answered from 1 to 3 hours by the most part (49.3%) of the interviewed people,confirming the character of permanence and not only of passing through the square. As longas locus, the central square, a typical feature of the urban identity of small municipalities, is areferring point for the citizen who passes by it, stands the daily routine of the urbe, scene oftraditional events of the city. It is in its surroundings in which is located the main commerce,the most important services and the major public buildings. The second hypothesis, whichpredicts the existence of alternative spaces of entertainment that compete with the squares inthe small municipalities, was also validated because the square ranks the fourth place of theplaces that usually attend the citizens in their free time in Engenheiro Beltrão and the fifthplace in Peabiru and Araruna, being overcome by places as: home of relatives and friends,snack bar/pizzeria, pubs, ice cream shop and countryside. In this study it was noticed theimportance of the squares in small municipalities as a space of socialization and thereforethey must be managed as such, and not simply be adopted serial and generalists measures,copied from larger urban centers, because the reality and ways of usage, appropriation andvalue attributed to these spaces by the citizen are distinct. It is inferred that the influx of thepopulation to the squares can be maximized from management initiatives that understand andsatisfy the peculiarities and dynamics of this urb.